PENINGKATAN KEMAMPUAN MEMBACA PEMAHAMAN DENGAN STRATEGI QUESTION ANSWER RELATIONSHIPS (QAR) PADA SISWA KELAS V SEKOLAH DASAR - Aan Khasanah; Isah Cahyani (Universitas Pendidikan Indonesia (UPI), 2013)
Thebackground of this study was the low of student’s reading comprehensionskill when answering questions, as well as retelling and summarizing thecontent of a text. This study was to improve the student’s readingcomprehension skill through QAR strategy as well as the teacher’sperformance. The research methodology used in this study is ClassroomActions Research which conducted in three cycles. The result of this studyshows that the average score of reading comprehension has increased. Theaverage score was increased from 57 to 70,20 in the cycle I, going up to 75,17in cycle II, and become 84,83 in cycle III. The application of QAR strategywith direct instruction from the teacher gives a positive effect, specifically, thestudents are active to do the pre-reading, reading and post-reading as well asmotivated to think hard by responding to the questions used in the QARstrategy. Thereby, the elementary school teachers are suggested to use theQAR strategy as one of the solutions in improving reading comprehensionskill.